Materials selection in mechanical design - Ashby, M. F. (Elsevier, BH, 2011)
"Understanding materials, their properties and behavior is fundamental to engineering design, and a key application of materials science. Written for all students of engineering, materials science and design, this book describes the procedures for material selection in mechanical design in order to ensure that the most suitable materials for a given application are identified from the full range of materials and section shapes available."--Resumé vydavatele
Keywords: materiály; průmyslový design; materials; industrial design; monografie; elektronické knihy; monographs; electronic books